Intravitreal ranibizumab for symptomatic drusenoid pigment epithelial detachment without choroidal neovascularization in age-related macular degeneration - Roberto Gallego-Pinazo (Dove Medical Press, 2011)
Roberto Gallego-Pinazo1,2, Ana Marina Suelves-Cogollos1, Ester Francés-Muñoz1, J María Millán2,3, J Fernando Arevalo4, J Luis Mullor5, Manuel Díaz-Llopis1,2,61Department of Ophthalmology, Hospital Universitario La Fe, Valencia, Spain; 2Centro de Investigación Biomédica en Red de Enfermedades Raras, Valencia, Spain; 3Department of Genetics, Hospital Universitario La Fe, Valencia, Spain; 4Retina and Vitreous Service, Clínica Oftalmológica Centro Caracas, Caracas, Venezuela; 5Unit of Experimental Ophthalmology, Fundación para la Investigación del Hospital Universitario La Fe, Valencia, Spain; 6University of Valencia, Faculty of Medicine, Valencia, SpainBackground: The aim of our study was to evaluate the functional and anatomic outcomes of intravitreal ranibizumab for the treatment of symptomatic drusenoid pigment epithelial detachment without choroidal neovascularization in age-related macular degeneration.Methods: This was a prospective, single-center, uncontrolled, interventional pilot study. Six consecutive eyes (six patients) with drusenoid pigment epithelial detachment with a visual acuity of 20/63 to 20/100 and no evidence of choroidal neovascularization in age-related macular degeneration participated. Patients were given at least one intravitreal ranibizumab injection and were followed for a mean of 66.67 ± 10.3 weeks. Main outcome measures included best-corrected visual acuity (BCVA) measured by Early Treatment Diabetic Retinopathy Study charts and optical coherence tomography, and central macular thickness measured by optical coherence tomography.Results: The mean number of intravitreal ranibizumab injections was 3.0 at the end of follow-up. Regarding BCVA and optical coherence tomography, 33.3% of eyes gained between 19 and 21 letters of BCVA, with a median decrease in central macular thickness of 21 µm. There was a statistically significant difference between baseline and final BCVA (P = 0.046). There was a positive correlation between intraretinal fluid by optical coherence tomography and improved BCVA after intravitreal ranibizumab. Metamorphopsia disappeared completely after the first injection in all subjects, with no further recurrences. No patient developed choroidal neovascularization or atrophic changes.Conclusion: Intravitreal ranibizumab demonstrated anatomic and functional benefit in patients with symptomatic drusenoid pigment epithelial detachment without choroidal neovascularization in age-related macular degeneration. Further long-term, randomized, controlled trials should be performed to confirm our preliminary results.Keywords: age-related macular degeneration, choroidal neovascularization, drusenoid pigment epithelial detachment, ranibizumab, soft drusen